Guidelines for predicting the remaining life of underground pipe networks that are subjected to the combined effects of external corrosion and internal pressure - Heyns, M. (University of Pretoria, 2013)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2002.